IoT-Based Electrical Protection and Monitoring System for Real-Time Detection of Current and Voltage Faults in Residential Electrical Installations - Fenti Amelia Sari; Naufal Akram; Arinda Frismelly; Syaiful Islami (Jurnal Teknik Elektro Indonesia, 2026)
Electrical disturbances such as overcurrent and overvoltage in residential electrical installations can lead to equipment damage, reduced operational efficiency, and increased safety risks if not addressed promptly. Conventional protection mechanisms are generally limited to localized interruption and lack real-time monitoring and remote communication capabilities. This study presents the design and implementation of an IoT-based electrical protection and monitoring system for real-time detection of current and voltage faults in residential electrical installations. The proposed system integrates a NodeMCU ESP8266 microcontroller, a PZEM-004T sensor module for measuring electrical parameters, a relay module for automatic load disconnection, and a mobile-based notification platform for remote monitoring. The system continuously measures voltage, current, power, and energy consumption while executing protective actions when abnormal thresholds are exceeded. An experimental approach was employed, including hardware design, prototype development, and performance evaluation under various load conditions. The results indicate that the system is capable of detecting electrical anomalies in real time with an average response time of 1 second and measurement accuracy reaching 98%. The relay mechanism successfully disconnected the load during fault conditions, while remote notifications enhanced user awareness and system accessibility. The proposed system demonstrates practical applicability as an intelligent protection framework for improving electrical safety and monitoring efficiency in residential environments.